High density lipoprotein metabolism in low density lipoprotein receptor-deficient mice(1) - Rinninger, Franz (J Lipid Res, 2014)
The LDL receptor (LDLR) and scavenger receptor class B type I (SR-BI) play physiological roles in LDL and HDL metabolism in vivo. In this study, we explored HDL metabolism in LDLR-deficient mice in comparison with WT littermates. Murine HDL was radiolabeled in the protein ((125)I) and in the cholesteryl ester (CE) moiety ([(3)H]). The metabolism of (125)I-/[(3)H]HDL was investigated in plasma and in tissues of mice and in murine hepatocytes. In WT mice, liver and adrenals selectively take up HDL-associated CE ([(3)H]). In contrast, in LDLR(−/−) mice, selective HDL CE uptake is significantly reduced in liver and adrenals. In hepatocytes isolated from LDLR(−/−) mice, selective HDL CE uptake is substantially diminished compared with WT liver cells. Hepatic and adrenal protein expression of lipoprotein receptors SR-BI, cluster of differentiation 36 (CD36), and LDL receptor-related protein 1 (LRP1) was analyzed by immunoblots. The respective protein levels were identical both in hepatic and adrenal membranes prepared from WT or from LDLR(−/−) mice. In summary, an LDLR deficiency substantially decreases selective HDL CE uptake by liver and adrenals. This decrease is independent from regulation of receptor proteins like SR-BI, CD36, and LRP1. Thus, LDLR expression has a substantial impact on both HDL and LDL metabolism in mice.